2020
DOI: 10.1097/md.0000000000018916
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of patients with acute pancreatitis complicated with hemorrhagic fever with renal syndrome and acute biliary pancreatitis

Abstract: Acute pancreatitis (AP) is a rare complication of hemorrhagic fever with renal syndrome (HFRS), and is difficult to diagnose. In this study, we retrospectively analyzed the clinical characteristics of 7 cases of HFRS complicated with AP and 105 cases of acute biliary pancreatitis (ABP). Medical records of 83 hospitalized patients with HFRS and 105 hospitalized patients with ABP in the affiliated Yijishan Hospital of Wannan Medical College were reviewed. The comparative analysis of patients between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The highest trypsinogen value in this cohort reached 33 ng/mL, also ruling out cases of acute pancreatitis. There are reports of Hantaan, Dobrava, and Seoul virus-induced HFRS accompanied with acute pancreatitis [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. In Europe, one study of 166 PUUV infected patients did not show any cases of pancreatitis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest trypsinogen value in this cohort reached 33 ng/mL, also ruling out cases of acute pancreatitis. There are reports of Hantaan, Dobrava, and Seoul virus-induced HFRS accompanied with acute pancreatitis [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. In Europe, one study of 166 PUUV infected patients did not show any cases of pancreatitis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results concerning pancreatic involvement in HFRS have been contradictory in previous studies. There are reports of a small series of HFRS accompanied by acute pancreatitis [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. In these studies, different hantaviruses are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Because HA is often related to AP but not limited to it, we were interested in the influence of HA on HFRS patients with and without AP. We found that a previous study analyzed HFRS complicated with AP in the Anhui Province of mid China showed that the incidence of AP in local HFRS patients was 8.43% [ 20 ], but in Albania, another country with a high incidence of HFRS, some researchers reported it was 11.1% [ 18 ]. In our study, this figure was 8.91%, which was similar to the former but not in accordance with the latter.…”
Section: Discussionmentioning
confidence: 99%
“…We inferred that this was probably due to the difference in the Hantavirus serotypes, socioeconomic situation, climatic factors, contact rate between rodents and humans, and the hygiene status between different regions. In the Anhui Province, the main serotypes of Hantaviruses were HTNV and the Seoul virus [ 20 ]; in Albania, it was the Dobrava-Belgrade virus [ 18 ], but in the Shaanxi Province (including Baoji city), it was HTNV only [ 11 ]. This means that compared with other Hantaviruses, HTNV may lead to a similar incidence of AP in west China as in mid China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation